High expression level of homocitrulline is correlated with seborrheic keratosis and skin aging - Juping Chen; Jun Liu; Zheng Wang; Jiandan Xu; Jia Tao; Hualing Li (Sociedade Brasileira de Dermatologia, 2023)
Abstract Backgroud Homocitrulline (Hcit), is involved in the pathological processes of some diseases. However, the role and function of Hcit (CBL) in human skin remains largely obscure. Objective To investigate the correlation of the level of Hcit in seborrheic keratosis, skin aging, and its clinical significance. Methods Immunohistochemistry was used to analyze the level of Hcit in skin lesions of seborrheic keratosis (SK), unaffected skin (distant 0.5 centimeters from SK lesion), and normal skin of healthy subjects in the control group. ELISA test was used to detect the serum level of CBL in SK patients and healthy subjects of different ages. Results Hcit was mainly localized in the nucleus of epidermal cells. In healthy control skin, the expression of Hcit increased with age and showed a positive correlation with age (the correlation coefficient was 0.806, p = 0.0002). The expressional level of Hcit in SK lesions was higher than that in healthy control skin (Z = −3.703, p = 0.0002). The serum level of CBL in healthy subjects and in SK patients increased with age (the correlation coefficient were 0.5763, p = 0.0032; 0.682, p = 0.004. respectively). The serum level of CBL in SK patients was higher than that in healthy subjects (Z = −2.19, p = 0.030). Study limitations The small serum sample size in the study. Conclusion The high expressional level of Hcit is correlated with seborrheic keratosis and skin aging. HCit may be one of the potential biomarkers of skin aging.